2003
DOI: 10.1007/s00296-003-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with infliximab decreases the CD4+CD28? T cell compartment in peripheral blood in patients with rheumatoid arthritis

Abstract: Chronic inflammatory syndromes such as rheumatoid arthritis (RA) are associated with high frequencies of CD4+CD28- T cells. The number of these cells is genetically determined and may also be a consequence of chronic exposure to tumor necrosis factor-alpha (TNFalpha). The aim of this study was to examine whether the reported efficacy of anti-TNFalpha therapy in RA involves a resurgence of T cell populations that re-express CD28. After 36-week therapy with infliximab, a significant decrease in CD4+CD28- T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…The CD4 ϩ CD28 null T-cell reduction observed in this study (33%) is similar to that reported in the study by Gerli et al, 21 which showed a 34% reduction in CD4 ϩ CD28 null T cells in patients with rheumatoid arthritis treated with infliximab. In the study by Pawlik et al, 22 a 36% reduction in CD4 ϩ CD28 null T cells was observed after treatment with infliximab. Because TNF-␣ downregulates the expression of CD28 on T cells at the transcriptional level, inhibition of TNF-␣ is likely to restore the presence of CD28 on cell surface by preventing TNF-␣-mediated downregulation of CD28 production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD4 ϩ CD28 null T-cell reduction observed in this study (33%) is similar to that reported in the study by Gerli et al, 21 which showed a 34% reduction in CD4 ϩ CD28 null T cells in patients with rheumatoid arthritis treated with infliximab. In the study by Pawlik et al, 22 a 36% reduction in CD4 ϩ CD28 null T cells was observed after treatment with infliximab. Because TNF-␣ downregulates the expression of CD28 on T cells at the transcriptional level, inhibition of TNF-␣ is likely to restore the presence of CD28 on cell surface by preventing TNF-␣-mediated downregulation of CD28 production.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of previous studies in patients with UA and in patients with rheumatoid arthritis, 17,19,21,22 we assumed that the percentage of CD4 ϩ CD28 null T cells likely to be found in our population was 10% (range, 5% to 14%). Moreover, in line with the findings reported by Gerli et al, 21 we assumed that a 34% reduction in CD4 ϩ CD28 null T cells after treatment with infliximab would have been significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4]13 Conflicting data can be found on the association between infliximab treatment and its potential effect on CD4 ϩ lymphocyte cell count. 14,15 Ferjolj et al 14 found a significant increase in the concentration of CD3 ϩ , CD4 ϩ , and CD8 ϩ T lymphocytes after infliximab treatment. However, a decrease of the CD4 ϩ CD28 − T-cell compartment in peripheral blood after infliximab therapy in patients with rheumatoid arthritis was reported.…”
Section: Commentmentioning
confidence: 99%
“…Eine therapeutische Blockade von TNFa führt zur Verbesserung der Vasomotorik [23]. Offen bleibt, inwieweit die unter TNFa-Blockade erfolgende Reduktion des Anteils klonal expandierter autoreaktiver T-Zellen für diese Beobachtung verantwortlich ist [63].…”
Section: Ra-spezifische Mechanismen Der Gefäßschädigungunclassified